The Effect of Vitamin D Supplementation on Rheumatoid Arthritis Patients: A Systematic Review and Meta-Analysis - Guan, Yuanyuan; Hao, Yang; Guan, Yun; Bu, Huaien; Wang, Hongwu (Frontiers in Medicine, 2020)
Objective Observational studies have shown that vitamin D levels are inversely related to rheumatoid arthritis activity, yet evidence from population interventions remains inconsistent. Methods The PubMed, Cochrane Library, Embase, CNKI, VIP, and Wanfang databases were searched for studies published before June 2020. Information was collected about the pain visual analogue scale (VAS), Disease Activity Score 28 (DAS28), serum vitamin D level, tender joint count (TJC), swollen joint count (SJC), erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and parathyroid hormone (PTH) research data. Results Six studies (n = 438) were included in the meta-analysis. Vitamin D supplementation resulted in a significant improvement in the DAS28 (weighted mean difference (WMD) = - 0.41, 95% CI (- 0.59, - 0.23), P < 0.001), ESR (WMD = - 3.40, 95% CI (- 6.62, - 0.18), P = 0.04) and TJC (WMD = - 1.44, 95% CI (- 2.74, - 0.14), P = 0.03) but not in other outcomes. According to the subgroup analyses, VAS and serum vitamin D were improved in the European ethnic subgroups. TJC and serum vitamin D were improved in the Asian ethnic subgroups. TJC and serum vitamin D were improved in the duration ≤ 12 w subgroups, and the VAS and DAS28 in the duration > 12 w subgroup were different from those of the control group. With a vitamin D dose ≤50,000 IU, only serum vitamin D and TJC improved, and with a vitamin D dose> 50,000 IU, the VAS and DAS28 improved. Conclusions Compared with control interventions, vitamin D supplementation seemed to be an effective intervention for patients with rheumatoid arthritis. Different doses of vitamin D and durations of intervention produce different effects.